SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT Di CREDIT UNION “PARDIS” DENGAN METODE FUZZY MAMDANI - Ertina Sabarita Barus; Hesalorafika Ginting (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
Credit is a loan by another party that will be returned at a certain time. In conducting credit analysis, if done properly can run as the first screening for the company to avoid bad credit, in the process of data processing candidate This creditor will appear vague variables that must be addressed by credit analyst.Credit Union "Pardis" is one of the financial institutions that provide credit loans. In this research used fuzzy mamdani method to solve the problem. The variables used for fuzzy calculations on this system are how income, savings balance and loan amount. Test results using Matlab Application.